Pojamide: An HDAC3-Selective Ferrocene Analogue with Remarkably Enhanced Redox-Triggered Ferrocenium Activity in Cells - Ocasio, Cory A.; Sansook, Supojjanee; Jones, Rhiannon; Roberts, Justin M.; Scott, Thomas G.; Tsoureas, Nikolaos; Coxhead, Peter; Guille, Matthew; Tizzard, Graham J.; Coles, Simon J.; Hochegger, Helfrid; Bradner, James E.; et al. (Organometallics, 2017)
A ferrocene containing o-aminoanilide, N1-(2-aminophenyl)-N8-ferrocenyloctanediamide (2b, Pojamide) displayed nanomolar potency vs HDAC3. In comparison to RGFP966, a potent and selective HDAC3 inhibitor, Pojamide displayed superior activity in HCT116 colorectal cancer cell invasion assays; however, TCH106 and romidepsin, potent HDAC1 inhibitors, outperformed Pojamide in cellular proliferation and colony formation assays. Together, these data suggest that HDAC1,3 inhibition is desirable to achieve maximum anticancer benefits. Additionally, we explored Pojamide-induced redox pharmacology. Indeed, treating HCT116 cells with Pojamide, SNP (sodium nitroprusside), and glutathione (GSH) led to greatly enhanced cytotoxicity and DNA damage, attributed to activation to an Fe(III) species.